SAVI Learning with Eco Edukit SITASUR to Support Junior High School Students' Conceptual Understanding of the Solar System - Fa'iza Aulia Pradanti; Dian Nugraheni; Erni Yulianti; Himawan Ganjar Prabowo (Jurnal Pendidikan Sains Indonesia, 2026)
The low level of students’ conceptual understanding of the solar system remains a pressing issue in science education, largely due to the dominance of lecture-based instruction and the limited use of concrete, interactive learning media. This study aims to develop the eco edukit SITASUR (sistem tata surya), an environmentally friendly learning medium based on the SAVI (somatic, auditory, visual, intellectual) approach, to enhance students’ comprehension of solar system concepts. Using the research and development (R&D) method with the ADDIE model, the product was validated by subject matter and media experts, yielding high feasibility scores of 87.36% and 81.31%, respectively. An effectiveness test, employing a one-group pretest–posttest design, demonstrated a significant improvement in learning outcomes, with average scores rising from 42.50 (pretest) to 81.23 (posttest). The resulting N-Gain score of 0.64 (moderate category) indicates that the eco edukit SITASUR is effective and suitable for junior high school science education. Beyond improving conceptual understanding, the media also fosters students’ environmental awareness